2013
DOI: 10.1111/j.1755-6686.2013.12000.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Intervention on Malnutrition Indicators in Patients on Haemodialysis

Abstract: Nutritional supplementation designed for haemodialysis, improved their nutritional status in the short term study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Moreover, in order to avoid flavor monotony; varying the types of herbs and spices, such as oregano, rosemary, dill, tarragon, cumin, garlic, paprika and onion, among others, can be used without compromising the energy, protein, Na, K and P content of the muffins. Other studies that developed non-industrialized food products for HD, although scarce, showed promising results in improving the nutritional status of patients that were malnourished [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in order to avoid flavor monotony; varying the types of herbs and spices, such as oregano, rosemary, dill, tarragon, cumin, garlic, paprika and onion, among others, can be used without compromising the energy, protein, Na, K and P content of the muffins. Other studies that developed non-industrialized food products for HD, although scarce, showed promising results in improving the nutritional status of patients that were malnourished [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…This result is in contrast to results obtained in a small, uncontrolled study that showed a beneficial effect of oral supplemental nutrition over 3 months in hemodialysis patients without signs of cachexia. 16 So far, the negative result of the present study…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies comparing different nutritional interventions, particularly in pre-dialysis CKD, are scarce, however Campbell et al (2008) found that a 12-week nutritional intervention programme improved nutritional status and HRQoL, possibly due to increased frequency of patient follow-up and more regular adjustments in nutritional treatment. The majority of other interventional studies included prevalent patients undergoing dialysis, and mostly investigated the potential benefit of nutritional supplements (Scott et al 2009;Roy et al 2013;Sezer et al 2014). The results of our study suggest that targeted nutritional advice, combined with increased exercise, led to maintenance of energy and protein intake and markers of nutritional status throughout the study period.…”
Section: Discussionmentioning
confidence: 61%